A QUARTET OF NEAR-EARTH ASTEROID BINARY CANDIDATES - Warner, Brian D. (Minor Planet Bull, 2015)
Analysis of CCD photometry observations at the Center for Solar System Studies-Palmer Divide Station (CS3-PDS) made in 2014 June-October found four main-belt binary candidates. 2012 Tantalus is a probable binary that shows a strong second period but no mutual events. (68348) 2001 LO7 is a probable binary, also showing a strong second period and no confirmed mutual events, but P(2) is a close to an integral multiple to P(1), which sometimes indicates a harmonic alias. (190208) 2006 AQ appears to be probable wide binary, showing a long period lightcurve superimposed by a short period, lower amplitude component. (276049) 2002 CE26 is a known binary (Shepard et al., 2004). Pravec et al. (2006) reported P(1) = 3.293 h with no indications of the satellite. The 2014 observations at CS3 initially led to P(1) = 3.088 h. After further analysis and confirmation of the longer period (Pravec, personal communications), a period of P(1) = 3.928 h was adopted. Unlike the earlier results, there were indications of a satellite with P(orb) = 16.26 h, which agrees with estimates for the orbital period based on the discovery radar observations. The lightcurve data, however, indicate a considerably larger satellite than indicated by radar.